Usefulness of Peak Flow Meter in Monitoring of Asthma Management in Pediatric Age Group - Afrah Tariq, Qaiser Shehzad Humayoun, Muhammad Hafeez, Israr Liaquat, Irum Tauhidi, Asad Shabbir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Toassess the incidence of usage of peak flow meter in the monitoring of asthma management in pediatric age group. Study Design: Descriptive case study Settings: Out Patient Department and Medical Ward of the Children’s hospital and The Institute of Child Health Lahorefor duration of six months from 1st October 2016 to 31st March 2017. Methodology: Patients admitted in the hospital fulfilling the criteria of inclusion were enrolled in the analysis. After taking informed consent from parents and approval from ethical committee their demographic information was recorded. The proforma was completed by the researcher. Follow up was done after one-week to label PFM usage. Results: Out of 210 cases, 55.24%(n=116) were between 8-12 years of age while 44.76%(n=94) were between 13-16 years of age, 50.95%(n=107) were male while 49.05%(n=103) were females with mean age 12.0+2.30 years. Frequency of usage of peak flow meter in the monitoring of asthma treatment was recorded in 18.57%(n=39) whereas 81.43%(n=171) had no PFM usage. Conclusion: We concluded that the frequency of usage of peak flow meter in the monitoring of asthma treatment in pediatric age group is similar to other studies but very few data on practices of asthma management in Pakistan and different protocols are used for asthma self-management which needs some-other studies so that more appropriate and evidenced based data may be collected for developing the local guidelines of self-management of asthma.